PERANAN PENYULUH PERTANIAN LAPANGAN (PPL) DALAM PENERAPAN PANCA USAHATANI PADI SAWAH SERTA HUBUNGANNYA DENGAN PRODUKTIVITAS DI KECAMATAN METRO BARAT KOTA METRO - Wayan Okiwidiyanti; Irwan Effendi; Rio Tedi Prayitno (Lampung University, 2019)
This study analyses the roles of AEWs, the level of implementation of the five-farming-system of paddy, the level of paddy productivity, the relationship between the roles of AEWs and the level of the implementation five, and the relationship between the implementation and paddy productivity. The research was conducted in the West Metro District of Metro City. The samples are 72 farmers of randomly selected respondents. Methods of data analysis using quantitative descriptive analysis, table analysis, and Rank Spearman correlation. The results indicated that AEWs have done their roles well, especially as educators who teach and educate farmers about the implementation of the five-farming-system of paddy. The five-farming-system of paddy has been applied well. Most farmers realize the importance of implementing the five-farming-system of paddy in accordance with the advice of AEWs to improve productivity. The average productivity of paddy is 6.46 ton/ha or in the medium class. The higher the role of AEWs, the higher the level of application of the five-farming-system of paddy. The higher the implementation of the five-farming-system of paddy, the higher the level of paddy productivity.Key words: AEWs, five-farming-system, productivity, role